Environmental contamination by geohelminths in squares of the municipality of Botucatu, Sao Paulo - Providelo, Gilson Avelino [UNESP]; de Oliveira, Raphaela Moreira [UNESP]; Santarém, Vamilton Alvares; Victoria, Cassiano [UNESP]; de Figueiredo Pantoja, José Carlos [UNESP]; dos Santos Schmidt, Elizabeth Moreira [UNESP] (Universidade Federal do Paraná, 2020)
Soil-transmitted helminths have great relevance in public health, due to the resistance of their infective forms (eggs and larvae) in the environment. Geohelminthiasis present a relevant capacity to cause morbidity and disability, but with low mortality. This study aimed to investigate the soil contamination by geohelminths in squares of the municipality of Botucatu-SP, identifying the prevalence of the main genera and their occurrence in squares of different areas of the municipality. The squares were cataloged and distributed among administrative regions. In this study soil samples were collected and evaluated by means of centrifugal-sedimentation techniques, centrifugal-flotation with zinc sulfate, and the Baermann-Moraes method in the search for eggs and larvae of geohelmints. The samples were carried out in two times: point I (from October to December of 2017) and point II (from February to March of 2018). From the analyzes of the soil samples, the occurrence of Toxocara sp. was observed in 17.7% and 23.3% respectively at moments I and II. The contamination by egg of Ancylostomatidae was observed in 6.6%, being found only in the time II collections. The results obtained in the present study demonstrated that the risk of human contamination by Toxocara spp. exists because it was the most prevalent geohelminth and the main risk factor observed and related to the presence of Toxocara spp. at the places investigated. Therefore, public health policies are necessary to avoid contamination of the human population that frequents these sites, combining approaches to prevent soil contamination and the control of geohelminthiasis in the population.
Contaminação ambiental por geo-helmintos em praças do município de Botucatu, São Paulo
Keywords: Ancylostomatidae; Soil contamination; Toxocara spp.; Zoonosis